(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Several reasonably cyclotomic sequences are constructed by cyclotomic classes with good pseudo-randomness property. During this paper, we derive the linear complexity of a new binary cyclotomic sequences of order 2lt over finite field having period pq. Our result shows that these sequences have high linear complexity, which can resist linear attack.